MAN AND WOMAN IDENTITY IN DALIHAN NA TOLU - Marpaung, Magdalena Br (International Journal of Humanity Studies (IJHS), 2023)
This research derived from the phenomenon that men of Toba Batak must be respected more and are treated differently from women. To define the truth of the phenomenon this study analysed the ideology of Toba Batak; dalihan na tolu which is composed by (1) somba marhula-hula, (2) elek marboru, and (3) manat mardongan tubu by analysing the syntactic and semantic structure of it and adapted the ecolinguistic approach to defined man and woman identity by Arran Stibbe. The syntactic and semantic analysis on dalihan na tolu defined the identity of men and women as follows: (a) men as brothers in Toba-Batak community are leader, decision makers, they are positioned the highest in the ideology and have more arguments in doing their responsibility to love sisters. (b) Women as sisters in Toba-Batak community are the second position in the ideology and for both syntactic and semantically are proved have to be strictly respect brothers, they have less argument to do it. However, men and women of Toba-Batak, due to their contribution to ‘manat mardongan tubu’ are positioned the same.